The Resistance Of The Cherokee Women Against "The Civilization Program" (1789 â1839) = Perlawanan Wanita Cherokee terhadap Program Civilization (1789-1839) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT This thesis is an effort to find out the roles of Cherokee women in the eighteenth century before the applicatioft of the civilization program. The objectives of the civilization program peculiarly for Cherokee women are explored here to reveal the roles of Cherokee women both which were changed or eradicated through the application of the civilization program. This thesis also aims to analyze the result of Cherokee women resistance towards the civilization program. In order to have a total comprehension on the issue, this thesis applies the interdisciplinary approach and studies the problems from the perspective of sociology, anthropology, literature, and religion. The sociological viewpoints enable the writer to comprehend the behavior and attitudes of Cherokee women in the era before the application of civilization program and when it is implemented. Anthropological viewpoint is used to find out the culture of Cherokees as non-literate society. Economical and political approaches are used to understand the condition of economic and politics when the civilization program took place. Religious perspectives are necessary to know the different viewpoints of Christianity and Cherokees religion especially about the position and men-women relationship. Literary approach is also employed to study the values of Cherokees that was represented in their myth, legend, song, and poetry. The result of this thesis indicates that the struggle of Cherokee women were successful in many ways, such as in defending their authority of teaching the custom of their tribe to their beloved children, preserving their roles in their fields as farmers, maintaining their participation in society meeting, and persisting their own religion. Their struggles were successful because they had high motivation to preserve their old and traditional culture. Their refusal was influenced by the fact that White's gender norms were not appropriate to them. It was derived from the consideration that their important roles and position would change and vanish. On the other hand, their struggle was less successful in opposing the removal policy. It was not caused by the weakening of their motivation in struggle. The environmental condition or the unsupporting members are the main factor of this failure.